Characterization and in ovo vascularization of a 3D-printed hydroxyapatite scaffold with different extracellular matrix coatings under perfusion culture - Floriana Burgio; Natalie Rimmer; Uwe Pieles; Johanna Buschmann; Marina Beaufils-Hugot (Biology Open, 2018)
For the fabrication of appropriate bone tissue-engineered constructs several prerequisites should be fulfilled. They should offer long-term stability, allow proper cell attachment and proliferation and furthermore be osteoinductive and easy to be vascularized. Having these requirements as background, we fabricated a novel porous 3D-printed hydroxyapatite (HA) scaffold and treated it with oxygen plasma (OPT). MG-63 pre-osteoblast-seeded bone constructs allowed good cell attachment and proliferation, which was even better when cultivated in a perfusion flow bioreactor. Moreover, the deposition of extracellular matrix (ECM) on the otherwise inorganic surface changed the mechanical properties in a favourable manner: elasticity increased from 42.95±1.09 to 91.9±5.1 MPa (assessed by nanoindentation). Compared to static conditions, osteogenic differentiation was enhanced in the bioreactor, with upregulation of ALP, collagen I and osteocalcin gene expression. In parallel experiments, primary human bone marrow mesenchymal stromal cells (hBMSCs) were used and findings under dynamic conditions were similar; with a higher commitment towards osteoblasts compared to static conditions. In addition, angiogenic markers CD31, eNOS and VEGF were upregulated, especially when osteogenic medium was used rather than proliferative medium. To compare differently fabricated ECMs in terms of vascularization, decellularized constructs were tested in the chorioallantoic membrane (CAM) assay with subsequent assessment of the functional perfusion capacity by MRI in the living chick embryo. Here, vascularization induced by ECM from osteogenic medium led to a vessel distribution more homogenous throughout the construct, while ECM from proliferative medium enhanced vessel density at the interface and, to a lower extent, at the middle and top. We conclude that dynamic cultivation of a novel porous OPT HA scaffold with hBMSCs in osteogenic medium and subsequent decellularization provides a promising off-the-shelf bone tissue-engineered construct.